How to Digitize Historical Pictorial Collections to Preserve Them in a Digital Life Cycle? - Pfeiffer, Michel (Monografija u povodu 20 godina rada Odjela za informacijske znanosti u Zadru, 2025)
The creation of collections in archives, libraries, museums, or documentation centres is and remains the linchpin of any practice-oriented information science studies programme. At the Swiss Institute of Information Science, the life cycle of analogue and digital cultural assets was studied early on. With the advent of digital long-term archiving, the need arose to understand and support objects and metadata from the “origin”, including during the digitization process. The establishment of a laboratory for the digitization of a wide range of cultural assets, from photography and written material to records and audiovisual media, was therefore a logical conclusion. This Lab made it possible to gain divergent perspectives in the complex process of the different models and life cycles. This paper will discuss the Metamorfoze Digitization standard as well as the technical Exchangeable Image File (Exif) Metadata Format, used for the digital life cycle aka. “digital long-term archive”. This article was originally published in German (Pfeiffer, 2020).